Techniques for Making Tea Bags from Medicinal Plants Camellia sinensis and Muntingia calabura in Preventing Diabetes Mellitus - Sitepu, Nadroh; Hidayah, Nurul; Noviar, Irma (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The development of original natural products known as ethnomedicine is expected to be useful as a health and treatment effort for the community. Dissemination of information through counselling and techniques for making Camellia sinensis and Muntingia calabura teas in preventing diabetes mellitus. This activity aims to increase the knowledge and ability of the community in utilizing and making research-based medicinal plants through demonstrations of techniques for making a combination of green tea with cherry leaves to the community. Community dedication was conducted on 33 resident respondents. In this activity, blood pressure, KGD and cholesterol levels were measured. Followed by providing information about diabetes-related symptoms and diabetes management and continued with the practice of making tea bags from green tea and cherry leaves technique.